Personal data leakage prevention system for network channels - Філоненко, Сергій Федорович; Мужик, Ігор Мирославович; Німченко, Тетяна Василівна (Ukrainian Scientific Journal of Information Security, 2014)
One of the actual problems of information security is information leakage, in particular personal data, using network channels. That’s why in this paper methods of threats minimizing to personal data have been considered. Tasks that need to be implemented for the personal data security in the formation and establishment of information security systems were considered. Their solutions in order to minimize threats to the personal data were considered. Prevent unauthorized leakage of personal data network channels requires the introduction of special systems of detection and blocking of sending such network channels have been shown. System to identify and prevent the leakage of personal data network channels was created. The basis of the system was based on the specific requirements for the management of personal information. This approach allows to identify the personal data in the network flow, the identification resolved and unresolved parcels such data network channels and prevent their unauthorized distribution network channels.